Aliphatic polyester, polyester composition containing same, and use thereof
Patent Information
- Application Number
- KR1020260042169
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-10
- Filing Date
- 2026-03-09
- Publication Date
- 2026-09-17
Smart Images

Figure PAT00004 
Figure PAT00005
Abstract
Description
Technology Field
[0001] The present invention belongs to the field of biodegradable polyester material technology, and specifically relates to an aliphatic polyester, a polyester composition containing the same, and applications thereof. Background Technology
[0002] Resource and environmental issues are one of the major challenges hindering the sustainable development of humanity. Among these, environmental pollution is a representative phenomenon of resource and environmental problems. For instance, general plastics, particularly packaging materials such as shopping bags, garbage bags, and agricultural mulch films, cause "white pollution," which severely impairs land-use efficiency, causes air and water pollution, and increases the risk of fire, thereby affecting life and health. "White pollution" refers to the phenomenon where plastics are indiscriminately discarded after use, making them difficult to decompose and consequently causing environmental pollution; therefore, the development of high-performance biodegradable materials is one of the important and essential means to solve the problem of white pollution.
[0003] Among biodegradable materials, naturally derived polymers such as starch are often used as fillers to reduce costs and improve film flexibility. However, commercially available starch-based biodegradable materials have low uniformity in mechanical performance; specifically regarding tearing performance in the transverse and longitudinal directions, these materials have the drawback of failing to withstand a certain load and tearing easily in the transverse direction. Furthermore, commercially available starch-based biodegradable materials often use aliphatic-aromatic polyesters as base resins, such as polybutylene adipate terephthalate (PBAT) and polybutylene sebacate terephthalate (PBSeT). Since aliphatic-aromatic polyesters contain a high content of terephthalate chain fragments in their molecular structure, it is generally difficult to satisfy household composting requirements when the product thickness is thick (>50 μm).
[0004] To address the anisotropy problem regarding the uniformity of mechanical performance of starch-based biodegradable materials, particularly tear performance in transverse and longitudinal directions, CN101522797A disclosed a biodegradable composition using starch with a particle size of less than 0.25 μm as the dispersed phase, thereby effectively improving the anisotropy problem of the material. However, as the starch particles become finer, the cost increases and dispersion is difficult in high-filling systems; furthermore, the composition does not effectively solve the problem of home composting of the material when PBAT is used as the base resin.
[0005] Based on this, developing an aliphatic polyester that has excellent uniformity of tear performance in the transverse and longitudinal directions, a high disintegration rate, and is suitable for manufacturing starch-based biodegradable materials to meet household composting requirements is an urgent task in this field. The problem to be solved
[0006] To address the shortcomings of existing technologies, the objective of the present invention is to provide an aliphatic polyester, a polyester composition containing the same, and uses thereof. The aliphatic polyester enables the production of starch-based biodegradable materials, thereby solving the problems of anisotropy and reduced uniformity in the tearing performance of starch-based biodegradable materials in the transverse and longitudinal directions, and thus meeting the requirements for household composting. means of solving the problem
[0007] To achieve the above objective, the following technical solution of the present invention is used:
[0008] In a first aspect, the present invention provides an aliphatic polyester comprising a diacid residue and a dihydric alcohol residue; the diacid residue comprises 61.2 to 69 mol% of succinic acid residues based on a total molar percentage content of a1), a1), and a2) of 100 mol%; and 31 to 38.8 mol% of sebacic acid residues based on a total molar percentage content of a2), a1), and a2) of 100 mol%; and the dihydric alcohol residue is selected from 1,4-butanediol residues in a molar amount equal to that of the diacid residue. In the present invention, by controlling the content of the succinic acid residue and the sebacic acid residue within the above range, a polybutylene succinate sebacate with uniform tear performance in the transverse and longitudinal directions can be obtained; By using the above-mentioned polybutylene succinate sebacate as a base resin to manufacture a starch-based biodegradable material, the problems of anisotropy and reduced uniformity in the tearing performance of the starch-based biodegradable material in the transverse and longitudinal directions are solved, and furthermore, the material can be guaranteed to have excellent tensile performance and decomposition performance; thereby, it can meet the requirements for household composting.
[0009] It must be clarified that the aforementioned “residue” refers to any organic structure introduced into the polymer chain by the relevant monomer through a condensation polymerization reaction, that is, an organic structure derived from the relevant monomer; for example, a diacid residue is the structure of a diacid monomer derived from an aliphatic polyester.
[0010] In the present invention, succinic acid and / or succinic acid derivatives are introduced into the polyester molecular chain through a polymerization reaction to form succinic acid residues; sebacic acid and / or sebacic acid derivatives are introduced into the polyester molecular chain through a polymerization reaction to form sebacic acid residues; in the chain fragment structure of the aliphatic polyester, if the content of succinic acid residues is high, the crystallization rate of the aliphatic polyester is fast and the degree of crystallinity is high, but the uniformity of tear performance in the transverse and longitudinal directions is reduced; and if the content of sebacic acid residues is high, the aliphatic polyester chain fragment becomes flexible, and the uniformity of tear performance in the transverse and longitudinal directions is likewise reduced. By controlling the molar ratio of succinic acid residues and sebacic acid residues within a specific range, it is ensured that the aliphatic polyester has excellent uniformity of tear performance in the transverse and longitudinal directions, while simultaneously having excellent tensile and decomposition performance of the material, without affecting the processing performance of the material.
[0011] In the present invention, the succinic acid derivative comprises an alkyl succinic acid ester, and, for example, the alkyl succinic acid ester may be at least one of succinic acid dimethyl ester, succinic acid diethyl ester, succinic acid dipropyl ester, succinic acid diisopropyl ester, succinic acid dibutyl ester, succinic acid diisobutyl ester, succinic acid dipentyl ester, succinic acid diisopentyl ester, and succinic acid dihexyl ester; the alkyl succinic acid ester may be an alkyl ester formed from succinic acid, or an alkyl ester formed from succinic acid anhydride, and preferably, a dimethyl succinic acid ester formed from succinic acid anhydride is used.
[0012] In the present invention, the sebacic acid derivative comprises an alkyl sebacic acid ester; exemplarily, the alkyl sebacic acid ester may be at least one of a dimethyl sebacic acid ester, a diethyl sebacic acid ester, a dipropyl sebacic acid ester, a diisopropyl sebacic acid ester, a dibutyl sebacic acid ester, a diisobutyl sebacic acid ester, a ditertbutyl sebacic acid ester, a dipentyl sebacic acid ester, a diisopentyl sebacic acid ester, and a dihexyl sebacic acid ester; and the alkyl sebacic acid ester may be an alkyl ester formed from sebacic acid, or an alkyl ester formed from sebacic anhydride.
[0013] Preferably, the diacid residue comprises 63.5 to 67.5 mol% of succinic acid residues based on 100 mol% of the total molar percentage content of a1), a1), and a2); and 32.5 to 36.5 mol% of sebacic acid residues based on 100 mol% of the total molar percentage content of a2), a1), and a2).
[0014] Preferably, the number average molecular weight (Mn) of the aliphatic polyester is 30,000 to 150,000, preferably 45,000 to 120,000, and more preferably 58,000 to 79,000.
[0015] In the present invention, the number average molecular weight can be measured by gel permeation chromatography (GPC), and monodisperse polystyrene is used as a standard material. If the number average molecular weight is excessively large or small, the uniformity of tear performance in the transverse and longitudinal directions of the aliphatic polyester is reduced.
[0016] In the present invention, the number average molecular weight can be controlled by controlling the polymerization temperature, time, and the addition of a crosslinking agent and a chain transfer agent.
[0017] Preferably, according to GB / T 32366-2015, the carboxyl group content of the aliphatic polyester is <35 mol / t, preferably <28 mol / t, and more preferably 5 to 20 mol / t.
[0018] In the present invention, if the carboxyl group content of the aliphatic polyester is high, the hydrolysis resistance and anti-aging performance are reduced; if the carboxyl group content is low, the biodisintegration rate is reduced and the cost is increased; the fewer the carboxylic acid terminals derived from unreacted dicarboxylic acid components, the lower the carboxyl group content of the aliphatic polyester; therefore, the carboxyl group content can be controlled by adjusting the degree of reaction or suppressing thermal decomposition by changing conditions such as the alcohol-to-acid ratio, polymerization temperature, and polymerization time; and also, the carboxyl group content can be controlled by controlling the type or number of impurities in the raw material, such as nitrogen compounds and metal ions.
[0019] Preferably, according to GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1.38 to 2.32 dL / g, preferably the intrinsic viscosity is 1.5 to 2.2 dL / g, more preferably the intrinsic viscosity is 1.58 to 2.11 dL / g, even more preferably the intrinsic viscosity is 1.67 to 2.02 dL / g, and particularly preferably the intrinsic viscosity is 1.82 to 1.95 dL / g.
[0020] In the present invention, the intrinsic viscosity of the aliphatic polyester is within the above range, so that the aliphatic polyester can have excellent uniformity of tearing performance in the transverse and longitudinal directions, and the mechanical properties of the molded body can be secured during molding processing, and also, the melt viscosity of the polyester does not overload the molding machine such as an extruder or injection molding machine during molding processing, thereby securing productivity.
[0021] In the present invention, the method for manufacturing the aliphatic polyester is not particularly limited, and any method capable of manufacturing an aliphatic polyester having the specific structure of the present invention is possible; preferably, the method for manufacturing the aliphatic polyester
[0022] (1) A step of obtaining an esterification product by reacting a divalent acid with a divalent alcohol;
[0023] (2) A step of obtaining a prepolymerized product by prepolymerizing the esterification product obtained in step (1);
[0024] (3) A step of obtaining a condensation polymerization product by reacting the prepolymerization product obtained in step (2) with the prepolymerization product obtained in step (2), i.e., obtaining an aliphatic polyester according to the present invention.
[0025] In the present invention, the diacid according to step (1) is succinic acid and / or a succinic acid derivative, sebacic acid and / or a sebacic acid derivative; the diacid may be used alone or may be a mixture of at least two; and the dialcohol is 1,4-butanediol.
[0026] In the present invention, the molar ratio of the dihydric alcohol and the dihydric acid is (1.2 to 3):1, and may be, for example, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1 or a range between any of the above values, and more preferably (1.4 to 2):1.
[0027] In the present invention, the origin of the succinic acid and / or succinic acid derivatives is not particularly limited and may be derived from bio-based succinic acid and / or succinic acid derivatives (i.e., the raw material for production is a biomass resource) or petroleum-based succinic acid and / or succinic acid derivatives (i.e., the raw material for production is a petroleum resource).
[0028] In the present invention, the reaction raw material according to step (1) further comprises a crosslinking agent; based on 100 wt% of the total mass of the aliphatic polyester, the mass of the crosslinking agent is 0 to 3 wt%; the crosslinking agent comprises at least one of a polyhydric alcohol, a polyhydric acid, or a polyhydric acid anhydride; exemplarily, the crosslinking agent comprises but is not limited to tartaric acid, citric acid or malic acid, trihydroxymethylpropane, trihydroxymethylethane, pentaerythritol, polyether triol, glycerol, 1,3,5-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid anhydride, 1,2,4,5-benzenetetracarboxylic acid, pyromellitic acid dianhydride, etc.
[0029] In the present invention, the reaction according to reaction (1) includes an esterification reaction and / or an ester exchange reaction; the temperature of the reaction is 150 to 220 ℃, the pressure is 0.7 to 1.3 bar, and the time is 2 to 6 h, and more preferably the temperature of the reaction is 165 to 210 ℃, the pressure is 0.8 to 1.2 bar, and the time is 3 to 5 h.
[0030] In the present invention, step (1) can be carried out in a single mixing device, and a divalent acid and a divalent alcohol are mixed to obtain a slurry, and then the temperature is raised to react.
[0031] In the present invention, the carboxyl group content of the esterification product according to step (1) is 240 to 570 mol / t, and more preferably 300 to 400 mol / t.
[0032] In the present invention, after the reaction according to step (1), a step of removing excess divalent alcohol by distillation is further included, and the removed divalent alcohol can be purified by distillation and recycled as a raw material, and the purity of the purified divalent alcohol is ≥95%.
[0033] In the present invention, the temperature of the prepolymerization reaction according to step (2) is 230 to 260 ℃, the pressure is 0.3 to 0.8 bar, and the time is 70 to 200 min; more preferably, the temperature of the reaction is 240 to 250 ℃, the pressure is 0.5 to 0.7 bar, and the time is 90 to 130 min.
[0034] In the present invention, step (2) can be carried out in a single pre-polymerization reactor.
[0035] In the present invention, the carboxyl group content of the prepolymerization product according to step (2) is 40 to 90 mol / t, and more preferably 55 to 75 mol / t.
[0036] In the present invention, the temperature of the condensation polymerization reaction according to step (3) is 235 to 260 ℃, the pressure is 0.2 to 5 mbar, and the time is 40 to 110 min; more preferably, the temperature of the reaction is 240 to 250 ℃, the pressure is 0.5 to 2 mbar, and the time is 70 to 100 min.
[0037] In the present invention, step (3) can be carried out in a sorter suitable for condensation polymerization reactions, such as a rotary type reactor, a cage type reactor, or a horizontal type reactor.
[0038] In the present invention, the reaction according to step (2) proceeds in the presence of a catalyst; said catalyst is a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound, or a titanium compound, more preferably a zinc compound, an aluminum compound, or a titanium compound, and most preferably a titanium compound; said titanium compound may be tetrabutyl titanate or tetraisopropyl titanate; and the titanium compound has a lower residue amount in the product or downstream product and lower toxicity compared to other compounds. It is particularly suitable for the manufacture of biodegradable polyesters, which can be added directly to the environment in the form of composting bags or coverings.
[0039] In the present invention, based on 100 wt% of the total mass of the reaction raw materials (divalent acid, divalent alcohol, and selective crosslinking agent), the total mass of the catalyst is 0.001 to 1 wt%.
[0040] In the present invention, other auxiliary agents may be added during the reaction of step (3) according to actual demand; said other auxiliary agents include, but are not limited to, catalyst deactivators, color stabilizers, activators, etc.
[0041] The catalyst deactivator comprises, but is not limited to, a phosphorus compound; the phosphorus compound comprises, but is not limited to, one or more of phosphoric acid and phosphoric acid; and when the mass of the prepolymerization product is based on 100 wt%, the mass of the catalyst deactivator is 0.001 to 0.1 wt%, preferably 0.01 to 0.05 wt%. For example, when a highly active titanium compound is selected and used as the catalyst, the catalyst deactivator may be added, wherein the molar ratio of Ti to P is (1.1 to 1.5):1, and particularly preferably the molar ratio of Ti to P is (1.1 to 1.3):1.
[0042] The above color stabilizer includes, but is not limited to, a phosphorus compound; the above phosphorus compound includes, but is not limited to, one or more of phosphoric acid, phosphorous acid, triphenyl phosphite, triphenyl phosphate, sodium hypophosphate, and sodium phosphate; the use of a color stabilizer generally reduces the condensation rate. Therefore, preferably, triphenyl phosphate, which does not have an adverse effect on the condensation rate, is used as a color stabilizer. Based on 100 wt% of the mass of the prepolymerization product, the mass of the color stabilizer is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%; and when the catalyst is selected from titanium compounds, the molar ratio of Ti to P is 1:(0.3 to 1.0), and particularly preferably the molar ratio of Ti to P is 1:(0.5 to 1.0).
[0043] The above-mentioned active agent includes, but is not limited to, a phosphorus compound; the above-mentioned phosphorus compound includes, but is not limited to, one or more of disodium hydrogen phosphate, calcium hypophosphate, calcium phosphate, calcium phosphate, sodium hypophosphate, sodium phosphate, triphenyl phosphate, triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, and tributyl phosphate. Based on 100 wt% of the mass of the prepolymerization product, the mass of the above-mentioned active agent is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%; and when the catalyst is selected from titanium compounds, the molar ratio of Ti to P is (1.0 to 1.5):1, and particularly preferably the molar ratio of Ti to P is (1.1 to 1.3):1.
[0044] More preferably, the color stabilizer and the active agent are used in combination, for example, triphenyl phosphate and disodium hydrogen phosphate.
[0045] In the present invention, a chain growth reaction is further included after the condensation polymerization reaction, that is, the product obtained from the condensation polymerization reaction (condensation polymerization product) reacts with a chain growth agent to obtain the aliphatic polyester.
[0046] In the present invention, the chain growth agent comprises one or more of isocyanate, peroxide, epoxide, oxazolin, oxazine, caprolactam, or carbodiimide.
[0047] In the present invention, the isocyanate may be an aromatic diisocyanate and / or an aliphatic diisocyanate, and the aromatic diisocyanate may be toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2′-diisocyanate, diphenylmethane 2,4′-diisocyanate, diphenylmethane 4,4′-diisocyanate, naphthalene 1,5-diisocyanate or dimethylbenzene diisocyanate; particularly preferably, diphenylmethane 2,2′-diisocyanate, diphenylmethane 2,4′-diisocyanate or diphenylmethane 4,4′-diisocyanate is used. The above aromatic diisocyanate may be a polynuclear aromatic diisocyanate, such as tri(4-isocyanato-phenyl)methane, containing three rings, which may be formed during the process of producing a diisocyanate having one or two rings. The above aliphatic diisocyanate may be a straight-chain or branched-chain alkylidene diisocyanate having 2 to 20 carbon atoms or a cycloalkylidene diisocyanate having 3 to 20 carbon atoms; exemplarily, the above aliphatic diisocyanate includes hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, or methylene di(4-isocyanatocyclohexane) diisocyanate. Particularly preferably, it is hexamethylene diisocyanate.
[0048] In the present invention, based on the total mass of the condensation polymerization product, the mass of the isocyanate may be 0.05 to 2 wt%, and particularly preferably 0.1 to 1.5 wt%.
[0049] In the present invention, the peroxide may be one or more of benzoyl peroxide, 1,1-di(tertbutyl peroxy)-3,3,5-trimethylcyclohexane, 1,1-di(tertbutyl peroxy)methylcyclododecane, 4,4-di(butyl peroxy)butyl pentanoate, dicumyl peroxide, tertbutyl peroxybenzoate, dibutyl peroxide, α,α-di(tertbutyl peroxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tertbutyl peroxy)hexane, 2,5-dimethyl-2,5-di(tertbutyl peroxy)hexane-3-phosphorus, or tertbutyl cumene peroxide.
[0050] In the present invention, based on the total mass of the condensation polymerization product, the mass of the peroxide may be 0.1 to 2 wt%, and particularly preferably 0.2 to 1 wt%.
[0051] In the present invention, the epoxide is one of a diglycidyl ether, hexamethylene diglycidyl ether, sorbitol diglycidyl ether, polyglyceryl polyglycidyl ether, pentaerythritol polyglycidyl ether, diglyceryl polyglycidyl ether, glyceryl polyglycidyl ether, trihydroxymethylpropane polyglycidyl ether, metaphenylene diglycidyl ether, neupentadiol diglycidyl ether, ethylene glycol diglycidyl ether, diglycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polybutylene glycol diglycidyl ether, styrene, and an epoxy-containing copolymer based on acrylate and / or methacrylate. It may include the above.
[0052] In the present invention, based on the total mass of the condensation polymerization product, the mass of the epoxide may be 0.1 to 2 wt%, and preferably 0.2 to 1 wt%.
[0053] In the present invention, the oxazoline may be one or more selected from 2,2′-di(2-oxazoline), di(2-oxazoline group)methane, 1,2-di(2-oxazoline group)ethane, 1,3-di(2-oxazoline group)propane, 1,4-di(2-oxazoline group)butane, 1,4-di(2-oxazoline group)benzene, 1,2-di(2-oxazoline group)benzene, or 1,3-di(2-oxazoline group)benzene. The above oxazine may be one or more selected from 2,2′-di(2-oxazine), di(2-oxazine)methane, 1,2-di(2-oxazine)ethane, 1,3-di(2-oxazine)propane, 1,4-di(2-oxazine)butane, 1,4-di(2-oxazine)benzene, 1,2-di(2-oxazine)benzene, or 1,3-di(2-oxazine)benzene. The above carbodiimide is N,N′-di-2,6-diisopropylphenyl carbodiimide, N,N′-di-ortho-methylphenyl carbodiimide, N,N′-diphenyl carbodiimide, N,N′-dioctyl decyl carbodiimide, N,N′-di-2,6-dimethylphenyl carbodiimide, N-methylphenyl-N′-cyclohexyl carbodiimide, N,N′-di-2,6-di-tertbutylphenyl carbodiimide, N,N′-di-2,4,6-triisobutylphenyl carbodiimide, diisopropyl carbodiimide, dimethyl carbodiimide, diisobutyl carbodiimide, dioctyl carbodiimide, tertbutyl isopropyl carbodiimide, di-β-naphthyl carbodiimide, or It may be one or more selected from di-tertbutyl carbodiimide.
[0054] In the present invention, based on the total mass of the condensation polymerization product, the mass of the oxazoline, oxazine, caprolactam, and carbodiimide is each independently 0.1 to 2 wt%, and preferably 0.2 to 1 wt%.
[0055] In the present invention, the temperature of the chain growth reaction is 170 to 240 ℃, and more preferably, the temperature of the reaction is 180 to 220 ℃; it can be carried out under superatmosphere or atmospheric pressure conditions, depending on the system used.
[0056] In the present invention, the chain growth reaction may be carried out in an extruder, a continuous mixer (list reactor), or a static mixer. The extruder may be a single-screw extruder or a twin-screw extruder; the static mixer may use SMR, SMX, or SMXL members or a combination thereof. Embodiments of the list reactor include a single-screw DISCOTHERM B, or a twin-screw CRP or ORP reactor, and preferably, the chain growth reaction is carried out in the extruder, and the residence time in the extruder is 2 to 15 min, more preferably 4 to 12 min.
[0057] In the present invention, the aliphatic polyester can also be prepared by the following method, namely, in step (1), succinic acid and / or a succinic acid derivative and sebacic acid and / or a sebacic acid derivative are each reacted with 1,4-butanediol to obtain two esters, and then subsequent prepolymerization reaction, condensation polymerization reaction and selective chain growth reaction are carried out on the two esters.
[0058] For example, the above manufacturing method specifically,
[0059] Step (1-1): A step of reacting succinic acid and / or a succinic acid derivative, 1,4-butanediol, and an optional crosslinking agent for 2 to 5 h under conditions of a temperature of 150 to 180 °C and a pressure of 0.7 to 1.1 bar to obtain an esterification product A having a carboxyl group content of 450 to 750 mol / t;
[0060] Step (1-2): reacting sebacic acid and / or a sebacic acid derivative with 1,4-butanediol at a temperature of 180–210 °C and a pressure of 0.6–1.1 bar for 3–6 h to obtain an esterification product B having a carboxyl group content of 300–620 mol / t; and then mixing the esterification product A and the esterification product B to proceed with a pre-polymerization reaction, a condensation polymerization reaction, and a selective chain growth reaction; wherein the conditions for the pre-polymerization, condensation polymerization reaction, and the selective chain growth reaction are selected within the same range as Step (2), Step (3), and the aforementioned chain growth reaction.
[0061] In a second aspect, the present invention provides a polyester composition, said polyester composition comprising polymer A and polymer B; said polymer A comprises an aliphatic polyester according to the first aspect.
[0062] Preferably, the polymer A further comprises a second polyester.
[0063] Preferably, the second polyester comprises at least one of polylactic acid (PLA), an aliphatic-aromatic polyester, or other aliphatic polyesters.
[0064] Preferably, the aliphatic-aromatic polyester comprises at least one of polybutylene succinate terephthalate (PBST), polybutylene adipate terephthalate (PBAT), polybutylene sebacate terephthalate (PBSeT), or polybutylene adipate furandicarboxylate (PBAF).
[0065] Preferably, the other aliphatic polyester comprises at least one of polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), or polybutylene sebacate (PBSe).
[0066] In the present invention, the second polyester may be selected from a corresponding polyester according to actual demand and is not limited to the polyester mentioned above.
[0067] Preferably, the polymer B comprises at least one of starch, cellulose, chitin, chitosan, alginate, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned materials.
[0068] In the present invention, the protein includes, but is not limited to, glutelin, zein, casein, collagen, etc.; the lignin includes unrefined lignin, refined hydrolyzed lignin, alkali-treated lignin, etc. Starch may be used in an allosteric form, a gelled form, or a filler form. The starch may exhibit a continuous phase, a dispersed phase, or a co-continuous form.
[0069] Preferably, the polyester further comprises an auxiliary agent.
[0070] In the present invention, the auxiliary agent may be added according to actual demand and includes, but is not limited to, at least one of an antioxidant, a lubricant, a light stabilizer, a release agent, or an antistatic agent.
[0071] In the present invention, there are no many restrictions on the type of auxiliary agent, and conventional auxiliary agents may be used. For example, the antioxidant may include any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 164, antioxidant DLTP, or antioxidant TPP, but is not limited thereto.
[0072] The above light stabilizer includes, but is not limited to, at least one of hindered amine-based light stabilizers (e.g., light stabilizer 770, light stabilizer 622, light stabilizer 944, etc.), benzophenone-based light stabilizers (e.g., UV531), or benzotriazole-based light stabilizers.
[0073] The above lubricant includes, but is not limited to, at least one of esters (e.g., polyethylene glycol ester, polyol ester), moncarbonate, ethylene bis stearamide, or polyethylene wax.
[0074] The above-mentioned release agent includes at least one of an inorganic release agent (e.g., talc powder, mica powder, clay, etc.), an organic release agent (e.g., fatty acid, paraffin, glycerol, petroleum jelly, etc.), or a polymeric release agent (e.g., silicone oil, polyethylene glycol, low molecular weight polyethylene, etc.), but is not limited thereto.
[0075] The above antistatic agent comprises, but is not limited to, at least one of a cationic antistatic agent (e.g., quaternary ammonium salt), anionic antistatic agent (e.g., alkylsulfonate, phosphate), amphoteric antistatic agent (e.g., amphoteric imidazoline-based compound), nonionic antistatic agent (e.g., hydroxyethyl alkylamine, fatty acid amides, polyoxyethylenes, polyol esters), or polymeric antistatic agent (e.g., polyethers).
[0076] As a preferred technical solution of the present invention, based on weight parts, the polyester composition comprises 50 to 95 parts of an aliphatic polyester (e.g., 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 parts or a range between any of the above figures, preferably 52 to 92 parts, more preferably 56 to 82 parts), 1 to 20 parts of a second polyester (e.g., 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 parts or a range between any of the above figures, preferably 1.5 to 15 parts, more preferably 2.5 to 8.5 parts), 1 to 30 parts of polymer B (e.g., 1, 2, 4, 6, 8, 10 parts, It includes 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, or a range between any of the above figures, preferably 9 to 27 parts, more preferably 21 to 26.5 parts) and 0 to 15 parts of an auxiliary agent (e.g., 1 part, 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, or a range between any of the above figures).
[0077] In the present invention, the method for manufacturing the polyester composition comprises the step of mixing polymer A, polymer B, and an optional auxiliary agent and extruding to obtain the polyester composition; the extruder includes a reactive extruder, and the extruder may be a single-screw extruder, a double-screw extruder, or a multi-screw extruder; the extrusion temperature is 140 to 220 ℃, and the screw rotation speed during extrusion is 200 to 500 rpm.
[0078] In a third aspect, the present invention provides a packaging film, said packaging film comprising an aliphatic polyester according to a first aspect or a polyester composition according to a second aspect.
[0079] In the present invention, the packaging film may have other substances added, such as coloring agents, pigments, and inorganic fillers, as needed; the pigments include, but are not limited to, titanium dioxide; and the inorganic fillers include, but are not limited to, talc powder, calcium carbonate, kaolin.
[0080] Preferably, the degree of orientation of the packaging film is 0.7 to 1.6, more preferably the degree of orientation is 0.8 to 1.4, and even more preferably the degree of orientation is 0.9 to 1.2.
[0081] In the present invention, the degree of orientation of the packaging film refers to the ratio of the tear strength in the longitudinal direction to the tear strength in the transverse direction; the higher the degree of orientation, the stronger the tear performance in the longitudinal direction becomes, but the tear performance in the transverse direction becomes weak, making it easy for rupture in the transverse direction to occur during use; the lower the degree of orientation, the weaker the tear performance in the longitudinal direction becomes, and the stronger the tear performance in the transverse direction becomes, making it easy for breakage in the longitudinal direction to occur during use; and the closer the degree of orientation is to 1, the more uniform the tear performance in the transverse and longitudinal directions of the material becomes.
[0082] In the present invention, the transverse and longitudinal Elmendorf tear strength of the packaging film is tested according to ASTM D1922, the thickness of the test sample is 55±3μm, and the orientation is the ratio of the longitudinal Elmendorf tear strength to the transverse Elmendorf tear strength.
[0083] In the present invention, according to ISO 527-2:2012, the longitudinal tensile strength of the packaging film is ≥18 MPa and the transverse tensile strength is ≥16 MPa; more preferably, the longitudinal tensile strength is ≥20 MPa and the transverse tensile strength is ≥18 MPa.
[0084] In the present invention, when the biodisintegration rate of the packaging film is ≥90%, the disintegration period is ≤21 weeks, and more preferably, the disintegration period is ≤15 weeks.
[0085] In the present invention, the biodisintegration rate and disintegration cycle of a packaging film are measured by the following method:
[0086] Measure the initial mass of a packaging film with dimensions of 10 cm × 10 cm and a thickness of 55 ± 3 μm and record it as m0; conduct a home composting test according to standard AS5810; sample and sort once a week; retain packaging film remaining on the sieve that is greater than or equal to 2 cm × 2 cm, wash off any residue on the film, dry it, weigh it, and record the sample mass as m n It is recorded as, and the biodisintegration rate of the packaging film is [(m0- m n If ) / m0]≥ 90%, record the corresponding disintegration period n.
[0087] In the present invention, the packaging film includes food packaging film, industrial packaging film, agricultural mulch film, shopping bag, garbage bag, etc.
[0088] The aliphatic polyester according to the present invention, the polyester composition comprising the aliphatic polyester, and the packaging film manufactured using the same are all biodegradable.
[0089] In the present invention, the material or mixture of materials has a biodegradability of at least 90% as defined in DIN EN 13432, and the material or mixture of materials has the characteristic of being "biodegradable."
[0090] According to DIN EN 13432, the composting process involves passing CO2-free air through matured compost while maintaining a specific temperature. Furthermore, biodegradability is defined as follows: the percentage of biodegradation expressed as the ratio of the net weight of CO2 emitted by the sample (after subtracting the CO2 emitted from the compost without the sample) to the maximum amount of CO2 the sample can emit (calculated based on the carbon content within the sample). After composting for several days, biodegradable polyesters and biodegradable polyester compositions typically show clear signs of degradation, such as fungal growth, cracking, and perforation.
[0091] ASTM D5338 and ASTM D6400 also describe other methods for determining biodegradability.
[0092] The numerical range according to the present invention includes not only the aforementioned listed point values but also any point values within the aforementioned numerical range that are not listed. Considering the limitation of the range and the brevity of the description, the present invention has not individually listed the specific point values included in the aforementioned range. Effects of the invention
[0093] Compared to existing technology, the beneficial effects of the present invention are as follows:
[0094] The aliphatic polyester provided in the present invention can obtain polybutylene succinate sebacate with uniform tear performance in the transverse and longitudinal directions by controlling the content of succinic acid and sebacic acid within a specific range; by using the polybutylene succinate sebacate as a base resin to manufacture a starch-based biodegradable material, the problems of anisotropy and reduced uniformity in the tear performance in the transverse and longitudinal directions of the starch-based biodegradable material are resolved, and furthermore, the material can be guaranteed to have excellent tensile performance and decomposition performance; thereby, the requirements for household composting can be met. Specific details for implementing the invention
[0095] The technical solution of the present invention is explained in more detail below through specific embodiments. As will be understood by those skilled in the art, the above embodiments are merely for the benefit of understanding the present invention and should not be interpreted as specific limitations on the invention.
[0096] In the present invention, all materials used are commercially available or manufactured by conventional methods, and unless otherwise specified, the materials used in the present invention are as follows.
[0097] 1,4-Butanediol: Purchased from Xinjiang Microchemical Co., Ltd.
[0098] Succinic acid: Purchased from Shandong Landian Bioscience & Technology Co., Ltd.
[0099] Sebacic acid: Purchased from Hengshui Jing Chemical Co., Ltd.
[0100] Glycerol: Purchased from Aladdin.
[0101] Tetrabutyl titanate: Purchased from Gyeonui Chemical Import & Export Co., Ltd.
[0102] Hexamethylene diisocyanate: Purchased from Aladdin.
[0103] Starch: Purchased from Shandong Shuguang Genengjin Corn Development Co., Ltd.
[0104] Polylactic acid: PLA, KB600 NF30, supplied by Zhuhai Golden Man Biomaterials Co., Ltd.
[0105] In the present invention, the test method for Mn, intrinsic viscosity, carboxyl group content, and molar content of succinic acid residues and sebacic acid residues in an aliphatic polyester is as follows.
[0106] 1. Mn was tested by gel permeation chromatography (GPC); the chromatography system was set to 40 °C, with a series-connected column of three per set (particle diameter 5 μm, porosity 500 each) , 1000 , 10000 Test using ) and a refractive index detector with chloroform as the eluent (elution flow rate 1 mL / min) and polystyrene as the standard.
[0107] 2. The intrinsic viscosity test is performed in reference to the standard GB / T 17931-1999. Specifically, 0.1250±0.0002g of the sample is placed in 25mL of a phenol / ortho-dichlorobenzene mixed solution with a weight ratio of 1:1 and heated until the sample is completely dissolved. After the sample is completely dissolved, the test is performed using a Ubbelohde viscometer at a test temperature of 25±0.05℃.
[0108] 3. The carboxyl group content is tested by referring to the standard GB / T 32366-2015, specifically by dissolving 1 g of the sample in 50 mL of a mixed solvent of phenol and trichloromethane in a volume ratio of 2:3; using an ethanol solution of potassium hydroxide with a concentration of 0.01 mol / L as the standard titration solution and a bromphenol blue solution with a concentration of 0.2% as the indicator; performing a blank test according to the method for testing the carboxyl group content of the sample; performing a parallel test on the sample twice, and the difference between the two results must be less than or equal to 2 mol / t, and the final result is the average value of the two test results.
[0109] 4. The molar percentage content is 1 Tested via the ¹H NMR method; specifically, 20 mg of the above-mentioned aliphatic polyester sample was taken, dissolved in 0.6 mL of deuterated chloroform, and then tested at room temperature using a Bruker AV 500 nuclear magnetic resonance spectrometer. 1¹H NMR was measured; integration was performed on the characteristic chemical shift peaks of the succinic acid residue and the sebacic acid residue (the characteristic chemical shift of the succinic acid residue is approximately 2.63 ppm, representing 4 hydrogens on the two methylene groups -CH2-CH2- in succinic acid; the characteristic chemical shift of the sebacic acid residue is approximately 1.30 ppm, representing 8 hydrogens on the four methylene groups -CH2-CH2-CH2- in the middle of sebacic acid), and the respective molar percentage contents of the succinic acid residue and the sebacic acid residue in the aliphatic polyester were calculated and obtained based on the peak area ratio; it should be noted that the contents of the succinic acid residue and the sebacic acid residue in the aliphatic polyester in Table 1 were calculated based on a total molar amount of 100 mol% of the succinic acid residue and the sebacic acid residue; For example, if the integral area of the succinic acid residue is I1 and the integral area of the sebacic acid residue is I2, the total molar percentage content of the succinic acid residue and the sebacic acid residue in the aliphatic polyester is I1 / (I1+I2)×100%.
[0110] Examples 1–13, Comparative Examples 1 and 2
[0111] Examples 1 to 13 and Comparative Examples 1 and 2 each provide an aliphatic polyester, and the molecular structure composition, Mn, acid value, and intrinsic viscosity of the aliphatic polyester are as shown in Table 1.
[0112] Table 1
[0113]
[0114] The method for manufacturing the aliphatic polyester provided in Examples 1 to 13 and Comparative Examples 1 and 2 is as follows.
[0115] Example 1
[0116] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0117] (1) 350 kg succinic acid, 323 kg sebacic acid, 575 kg 1,4-butanediol and 2.76 kg glycerol are physically mixed, and after mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 4 h under conditions of a temperature of 200 ℃ and a pressure of 1.1 bar to obtain an esterification product;
[0118] (2) The esterification product obtained in step (1) is transferred to an upright reactor capable of stirring, and 1.1 kg of tetrabutyl titanate is added to carry out a prepolymerization reaction for 110 min at a temperature of 243 ℃ and a pressure of 0.60 bar to obtain a prepolymerization product;
[0119] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 80 minutes at a temperature of 245 ℃ and a pressure of 1.2 mbar to obtain an aliphatic polyester.
[0120] Example 2
[0121] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0122] (1) 373 kg succinic acid, 300 kg sebacic acid, 575 kg 1,4-butanediol and 2.76 kg glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 h under conditions of a temperature of 190 ℃ and a pressure of 1.1 bar to obtain an esterification product;
[0123] (2) The esterification product obtained in step (1) is transferred to an upright reactor capable of stirring, and 1.1 kg of tetrabutyl titanate is added to carry out a prepolymerization reaction for 120 min at a temperature of 240 ℃ and a pressure of 0.7 bar to obtain a prepolymerization product;
[0124] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 100 min at a temperature of 245 ℃ and a pressure of 1.1 mbar to obtain an aliphatic polyester.
[0125] Example 3
[0126] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0127] (1) 330 kg succinic acid, 343 kg sebacic acid, 575 kg 1,4-butanediol and 2.76 kg glycerol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 3.5 h under conditions of a temperature of 180 ℃ and a pressure of 0.9 bar to obtain an esterification product;
[0128] (2) The esterification product obtained in step (1) is transferred to an upright reactor capable of stirring, and 1.1 kg of tetrabutyl titanate is added to carry out a pre-condensation reaction for 100 min at a temperature of 242 ℃ and a pressure of 0.6 bar to obtain a pre-polymerization product;
[0129] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 85 minutes at a temperature of 243 ℃ and a pressure of 1.3 mbar to obtain an aliphatic polyester.
[0130] Example 4
[0131] A method for manufacturing the above-mentioned aliphatic polyester is provided, and the distinction from Example 1 is as follows. In step (1), there is no glycerol, and the condensation polymerization reaction in step (3) is carried out for 60 min under conditions of a temperature of 243 °C and a pressure of 1.1 mbar. Additionally, the condensation polymerization product obtained after the condensation polymerization reaction in step (3) and hexamethylene diisocyanate (content is 0.3 wt% of the mass of the condensation polymerization product) are extruded in a reactive extruder at a temperature of 200 °C with a residence time of 8 min, and all other raw materials, steps, and polymerization processes are the same as in Example 1.
[0132] Example 5
[0133] A method for manufacturing the above-mentioned aliphatic polyester is provided, the difference from Example 1 is as follows, and step (1) comprises the following steps:
[0134] (1-1) 350 kg succinic acid, 300 kg 1,4-butanediol, and 2.76 kg glycerol are physically mixed, and after mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 4 hours under conditions of a temperature of 165 ℃ and a pressure of 1.1 bar to obtain esterification product A;
[0135] (1-2) 323 kg of sebacic acid and 275 kg of 1,4-butanediol are physically mixed, and after the mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 3 hours at a temperature of 200 ℃ and a pressure of 0.9 bar to obtain esterification product B; after mixing esterification product A and esterification product B, steps (2) and (3) are carried out, and other raw materials, steps and manufacturing methods are all the same as in Example 1.
[0136] Example 6
[0137] A method for manufacturing the above-mentioned aliphatic polyester is provided, which is distinguished from Example 1 as follows. The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 70 minutes under conditions of a temperature of 250 °C and a pressure of 1.4 mbar, and all other raw materials, steps, and polymerization processes are the same as in Example 1.
[0138] Example 7
[0139] A method for manufacturing the above-mentioned aliphatic polyester is provided, which is distinguished from Example 4 as follows. In step (3), the condensation polymerization product obtained after the condensation polymerization reaction and hexamethylene diisocyanate (content is 0.46 wt% of the mass of the condensation polymerization product) are extruded in a reactive extruder at a temperature of 210 ℃ with a residence time of 5 min, and all other raw materials, steps, and polymerization processes are the same as in Example 4.
[0140] Example 8
[0141] The above method for manufacturing an aliphatic polyester is provided, and the difference from Example 1 is as follows. In step (1), the amount of glycerol added is 2.45 kg, and an esterification reaction is carried out for 3 h under conditions where the esterification temperature is controlled to 190°C and the pressure to 1.0 bar to obtain an esterification product. In step (3), a condensation polymerization reaction is carried out for 70 min under conditions where the temperature is 243°C and the pressure is 1.0 mbar, and all other raw materials, steps, and polymerization processes are the same as in Example 1.
[0142] Example 9
[0143] A method for manufacturing the above-mentioned aliphatic polyester is provided, and the distinction therefrom from Example 1 is as follows. In step (3), the prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 50 min at a temperature of 248 °C and a pressure of 1.2 mbar. In step (4), the condensation polymerization product obtained in step (3) and hexamethylene diisocyanate (content is 0.25 wt% of the mass of the condensation polymerization product) are extruded in a reactive extruder at a temperature of 220 °C with a residence time of 10 min, and all other raw materials, steps, and polymerization processes are the same as in Example 1.
[0144] Example 10
[0145] A method for manufacturing the above-mentioned aliphatic polyester is provided, and the difference from Example 1 is as follows. In step (1), there is no glycerol, and an esterification reaction is carried out for 3 hours under conditions where the esterification temperature is controlled to 180°C and the pressure to 1.1 bar to obtain an esterification product, and in step (3), a condensation polymerization reaction is carried out for 75 minutes under conditions where the temperature is 245°C and the pressure is 1.5 mbar, and all other raw materials, steps, and polymerization processes are the same as in Example 1.
[0146] Example 11
[0147] A method for manufacturing the above-mentioned aliphatic polyester is provided, and the distinction therefrom from Example 1 is as follows. In step (3), the prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 45 minutes under conditions of a temperature of 242 °C and a pressure of 1.4 mbar. In step (4), the condensation polymerization product obtained in step (3) and hexamethylene diisocyanate (content of 0.70 wt% of the mass of the condensation polymerization product) are extruded in a reactive extruder at a temperature of 220 °C with a residence time of 13 minutes, and all other raw materials, steps, and polymerization processes are the same as in Example 1.
[0148] Example 12
[0149] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0150] (1) 350 kg succinic acid, 323 kg sebacic acid, 575 kg 1,4-butanediol and 12.0 kg glycerol are physically mixed, and after mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 2 h under conditions of a temperature of 180 ℃ and a pressure of 1.1 bar to obtain an esterification product;
[0151] (2) The esterification product obtained in step (1) is transferred to an upright reactor capable of stirring, and 0.8 kg of tetrabutyl titanate is added to carry out a prepolymerization reaction for 120 min at a temperature of 235 ℃ and a pressure of 0.5 bar to obtain a prepolymerization product;
[0152] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 70 minutes at a temperature of 244 ℃ and a pressure of 0.9 mbar to obtain an aliphatic polyester.
[0153] Example 13
[0154] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0155] (1-1) 350 kg succinic acid, 300 kg 1,4-butanediol, and 0.5 kg pentaerythritol are physically mixed, and after mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 3 h under conditions of a temperature of 160 ℃ and a pressure of 1.1 bar to obtain esterification product A;
[0156] (1-2) 323 kg of sebacic acid and 275 kg of 1,4-butanediol were physically mixed, and after mixing was complete, the mixture was transferred to an esterification reactor and the esterification reaction was carried out for 4 h under conditions of a temperature of 190 ℃ and a pressure of 1.0 bar to obtain esterification product B;
[0157] (2) Mix the esterification product A obtained in step (1) and the esterification product B obtained in step (2), transfer the mixture to an upright reactor capable of stirring, add 1.0 kg of tetrabutyl titanate, and carry out a prepolymerization reaction for 105 min at a temperature of 240 ℃ and a pressure of 0.7 bar to obtain a prepolymerization product;
[0158] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 70 min at 242 ℃ and 1.1 mbar to obtain a condensation polymerization product;
[0159] (4), the condensation polymerization product obtained in step (3) and hexamethylene diisocyanate (content is 0.57 wt% of the mass of the condensation polymerization product) are extruded in a reactive extruder at a temperature of 180 ℃ with a residence time of 11 min, and the other raw materials, steps and polymerization process are all the same as in Example 1.
[0160] Comparative Example 1
[0161] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0162] (1) 350 kg succinic acid, 245 kg sebacic acid, 534 kg 1,4-butanediol and 2.46 kg glycerol are physically mixed, and after mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 3.5 h under conditions of a temperature of 200 ℃ and a pressure of 1.1 bar to obtain an esterification product;
[0163] (2) The esterification product obtained in step (1) is transferred to an upright reactor capable of stirring, and 0.92 kg of tetrabutyl titanate is added to carry out a prepolymerization reaction for 120 min at a temperature of 245 ℃ and a pressure of 0.52 bar to obtain a prepolymerization product;
[0164] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 90 minutes at a temperature of 246 ℃ and a pressure of 1.3 mbar to obtain an aliphatic polyester.
[0165] Comparative Example 2
[0166] The present invention provides a method for manufacturing the above-mentioned aliphatic polyester, specifically comprising the following steps:
[0167] (1) 250 kg succinic acid, 345 kg sebacic acid, 480 kg 1,4-butanediol and 2.46 kg glycerol are physically mixed, and after mixing is complete, the mixture is transferred to an esterification reactor and the esterification reaction is carried out for 4 h under conditions of a temperature of 190 ℃ and a pressure of 1.1 bar to obtain an esterification product;
[0168] (2) The esterification product obtained in step (1) is transferred to an upright reactor capable of stirring, and 0.92 kg of tetrabutyl titanate is added to carry out a prepolymerization reaction for 130 min at a temperature of 243 ℃ and a pressure of 0.52 bar to obtain a prepolymerization product;
[0169] (3) The prepolymerization product obtained in step (2) is transferred to a horizontal reactor capable of stirring, and a condensation polymerization reaction is carried out for 80 minutes at a temperature of 246 ℃ and a pressure of 1.2 mbar to obtain an aliphatic polyester.
[0170] Application Examples 1–13, Comparative Application Examples 1, 2
[0171] Application Examples 1 to 13 and Comparative Application Examples 1 and 2 each provide a polyester composition, wherein the polyester composition comprises, based on weight parts, 63 parts of aliphatic polyester, 2 parts of polylactic acid, 27 parts of starch, 4 parts of glycerol, 3 parts of water, and 1 part of other auxiliary agents (including 0.5 parts of a complex antioxidant composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and 0.5 parts of the lubricant ethylene bis stearamide); the aliphatic polyester is provided in Examples 1 to 13 and Comparative Examples 1 and 2, respectively; and the method for manufacturing the polyester composition comprises mixing each component according to the mixing amount, adding it to a double screw extruder (length-to-diameter ratio 48:1; diameter 40 mm), melt-mixing, and then extruding to produce a granule form; The extrusion temperatures are sequentially 120 ℃ (Section 1), 160 ℃ (Section 2), 180 ℃ (Sections 3–9), 170 ℃ (Section 10), 170 ℃ (Section 11), and 190 ℃ (Head); the screw rotation speed is 380 rpm, and the vacuum is -0.60 kg / cm². 2 The polyester composition is obtained by adjusting the amount.
[0172] Performance test
[0173] Polyester compositions provided in Application Examples 1 to 13 and Comparative Application Examples 1 to 2 were blow-film processed to obtain packaging films; the uniformity of tear resistance performance, disintegration cycle, and tensile strength of the packaging films were tested; and the specific test results are as shown in Table 2.
[0174] Here, the process parameters for blow film processing are: the screw length-to-diameter ratio is 32:1, a spiral-type die head is used, the air ring is a double-outlet type air ring, the blow film processing temperature set value is 140 ℃, the blow expansion ratio is 3.5, and the blow film thickness is 55±3μm, and then the uniformity of tear resistance performance, disintegration cycle, and tensile strength are tested.
[0175] (1) Tear strength uniformity: Transverse direction of the sample (ε) according to ASTM D1922-2015 standard under conditions of 25±5℃ and 55±5% humidity TD ) and vertical direction (ε MD Test the Elmendorf tear strength of ), calculate the degree of orientation; degree of orientation = ε MD / ε TD am.
[0176] (2) Disintegration period:
[0177] Weigh the sample, mold the aliphatic polyester to produce a 10cm × 10cm product, obtain the initial mass of the sample and record it as m0, conduct a home composting test according to standard AS5810, sample and sort the sample once a week, retain packaging film remaining on the sieve with a length × width greater than or equal to 2 cm × 2 cm, wash and dry the residue on the packaging film, weigh it, and record the sample mass as m n It is recorded as, and the biodisintegration rate of the sample is [(m0- m n If ) / m0]≥ 90%, record the corresponding disintegration period n.
[0178] (3) Tensile strength: Tested according to ISO 527-2:2012.
[0179] Table 2
[0180]
[0181] As can be seen from Table 2, by controlling the molar content of succinic acid and sebacic acid provided in the present invention within a specific range, the aliphatic polyester has excellent uniformity in terms of tearing performance in the transverse and longitudinal directions and the degree of orientation approaches 1; furthermore, it has excellent tensile performance and a high biodisintegration rate under home composting conditions and a short disintegration cycle, thereby satisfying home composting requirements.
[0182] The specific embodiments described above further explain the purpose, technical measures, and beneficial effects of the present invention in greater detail. It should be understood that the foregoing description is merely a specific embodiment of the present invention and does not limit the invention, and that all modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.
Claims
Claim 1 An aliphatic polyester comprising a diacid residue and a dihydric alcohol residue; wherein the diacid residue comprises 61.2 to 69 mol% of succinic acid residues based on a total molar percentage content of a1), a1), and a2) of 100 mol%; and 31 to 38.8 mol% of sebacic acid residues based on a total molar percentage content of a2), a1), and a2) of 100 mol%; and wherein the dihydric alcohol residue is selected from 1,4-butanediol residues in a molar amount equal to that of the diacid residue. Claim 2 The aliphatic polyester according to claim 1, characterized in that the diacid residue comprises 63.5 to 67.5 mol% of succinic acid residues based on 100 mol% of the total molar percentage content of a1), a1), and a2); and 32.5 to 36.5 mol% of sebacic acid residues based on 100 mol% of the total molar percentage content of a2), a1), and a2). Claim 3 An aliphatic polyester according to claim 1 or 2, characterized in that the number average molecular weight of the aliphatic polyester is 30,000 to 150,000, preferably 45,000 to 120,000, and more preferably 58,000 to 79,000. Claim 4 An aliphatic polyester according to any one of claims 1 to 3, wherein, according to GB / T 32366-2015, the carboxyl group content of the aliphatic polyester is <35 mol / t, preferably <28 mol / t, and more preferably 5 to 20 mol / t. Claim 5 An aliphatic polyester according to any one of claims 1 to 4, characterized in that, according to GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1.38 to 2.32 dL / g, and preferably the intrinsic viscosity is 1.5 to 2.2 dL / g. Claim 6 A polyester composition characterized in that, in the polyester composition, the polyester composition comprises polymer A and polymer B; and the polymer A comprises an aliphatic polyester according to any one of claims 1 to 5. Claim 7 In claim 6, the polymer A further comprises a second polyester; preferably, the second polyester comprises at least one of polylactic acid, an aliphatic-aromatic polyester, or other aliphatic polyesters; Preferably, the aliphatic-aromatic polyester comprises at least one of polybutylene succinate terephthalate, polybutylene adipate terephthalate, polybutylene sebacate terephthalate, or polybutylene adipate furandicarboxylate; preferably, the other aliphatic polyester comprises at least one of polybutylene succinate, polybutylene succinate adipate, or polybutylene sebacate; preferably, the polymer B comprises at least one of starch, cellulose, chitin, chitosan, alginate, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned material; and preferably, the polyester composition further comprises an auxiliary agent. Claim 8 A polyester composition according to claim 6 or 7, characterized in that, based on weight parts, the polyester composition comprises 50 to 95 parts of an aliphatic polyester, 1 to 20 parts of a second polyester, 1 to 30 parts of polymer B, and 0 to 15 parts of an auxiliary agent. Claim 9 A packaging film characterized in that, in the packaging film, the packaging film comprises an aliphatic polyester according to any one of claims 1 to 5 or a polyester composition according to any one of claims 6 to 8. Claim 10 A packaging film according to claim 9, characterized in that the degree of orientation of the packaging film is 0.7 to 1.6, more preferably 0.8 to 1.4, and even more preferably 0.9 to 1.2.
